Can feline (Felis catus) flat and long bone morphometry predict sex or skull shape? - Burin Boonsri (2019)
© 2019, Japanese Association of Anatomists. This study demonstrates sexual dimorphism in feline bones based on morphometric analysis of dried flat bones (scapula and os coxa) and long bones (humerus, radius, ulna, femur, tibia, and fibula) of 92 felines (50 male, 42 female). A total of 58 parameters (flat bones: scapula = 4 and os coxa = 7; long bones: humerus = 8, radius = 9, ulna = 10, femur = 9, tibia = 7, and fibula = 4) were measured using a digital vernier caliper. Twenty-three parameters were found to be significantly different between cats of different sexes and skull shapes. The correlation between the cephalic index and most parameters was negative. Analysis of bone morphometry enabled us to estimate both sex and skull shape with accuracy of up to 96 % and 71 %, respectively, through a stepwise logistic regression model and a stepwise discriminative analysis model. The stepwise logistic regression model was determined to be most suitable for classifying two categories of data and had higher prediction accuracy rate.